USERS’ SATISFACTION IN PILOT TESTING OF THE EDUCATION INNOVATION (ONLINE LEARNING MEDIA) FOR STUDENTS IN MASTER OF BUSINESS ADMINISTRATION, DUSIT THANI COLLEGE - Booranavitayaporn, Suphicha (Dusit Thani College Journal, 2021)
This research was aimed to study the pilot testers’ opinion and satisfaction in the online learning media for students in Master of Business Administration, Dusit Thani College following the education innovation concept in 5 aspects, consisting of 1) the efficiency, the effectiveness, the quality, and the appeal of the online learning media 2) the satisfaction on the online learning media 3) the factors that significantly influence the satisfaction in online learning media and 4)the problems faced during the pilot-testing and the suggestions which can be used to develop the future online learning media. This study was a mixed method research. For the quantitative research, online questionnaires were conducted from 46 pilot testers. Descriptive Statistics were used in the analysis. The hypotheses were tested using Independent T-Test, One-way ANOVA and Multiple Regression Analysis. For the qualitative research, in-depth interviews were conducted. The key informants were 5 academic experts and 10 MBA students. Results of the study showed that the pilot testers agreed at the high level on the efficiency, the effectiveness, the quality, the appeal and the overall satisfaction on the online learning media. Different gender and age of the pilot testers showed no significant difference in the overall satisfaction on the online learning media at P-value 0.05. Efficiency and appeal of the online learning media significantly influenced the pilot testers’ overall satisfaction on the online learning media at P-value 0.05. From in-depth interview, the pilot testers were satisfied with the comprehensiveness and the length of the content. They were able to learn anywhere and review the content for many times. There was no report about any technical problems occurred. For the suggestions, the result showed that the online learning media should be more appealing.